EXAMINATION OF FACTORS ASSOCIATED WITH ATTITUDES TOWARD SEEKING PROFESSIONAL PSYCHOLOGICAL HELP AMONG UNIVERSITY STUDENTS IN KAZAKHSTAN - Utayeva, Ainura (Nazarbayev University School of Medicine, 2025)
Introduction The issue of the high prevalence of mental illnesses among students in Kazakhstan requires attention from stakeholders on improving psychological help services. Therefore, this study aimed to discover the factors influencing mental health service utilization among students. The significance of this study is an examination of correlates influencing the attitudes of students to seek psychological help related not only to factors explored by global literature but also aspects reflecting local context comparing public and private psychological healthcare. Methods A cross-sectional survey was conducted among 206 students of higher education aged 18–36 years. Data were collected using the Attitudes Toward Seeking Professional Psychological Help (ATSPPH-SF) scale, along with additional questions related to sociodemographic characteristics, satisfaction with past psychological services, concerns about public and private healthcare, and perceived social stigma. Simple and multiple linear regression analyses were performed to identify predictors of help-seeking attitudes with a statistical significance of p-value < 0.05. Results The mean ATSPPH score was 18.3 out of 30, indicating a moderate level of helpseeking attitudes among students of Kazakhstan. Higher education levels showed a coefficient of β = 5.6, with p-value < 0.001, the greater satisfaction with previous psychological services also had a positive coefficient of β = 4.6 (p-value < 0.002). Whereas perceived social stigma indicated a negative coefficient of β = -0.4 (p-value < 0.004). Concerns about the quality of care in state polyclinics were found to be positively correlated with attitudes (β = 2.9, p-value < 0.009). Gender differences were observed in bivariate analysis but became non-significant in the adjusted model (β = -1.5, p-value < 0.125). 5 Conclusion The research explored multiple determinants of professional psychological helpseeking attitudes which included educational background as well as satisfaction with received mental health services and perceptions of social stigma. More favorable attitudes emerged from individuals who obtained post-secondary education along with positive help-seeking past experiences and lower social stigma perceptions. People expressed doubts about choosing public services instead of private ones because they feared professionalism issues as well as service quality deficiencies and concerns about confidentiality protection. Better quality services combined with higher ethical standards and social stigma reduction initiatives will promote people to seek professional help.
Keywords: psychological help-seeking; attitudes; mental health; social stigma; Kazakhstan; students; satisfaction; state-run and private psychological services; type of access: embargo